Fasilitas Online Trading Dan Modal Minimal Investasi Pada Minat Investasi Mahasiswa - Norma Dewi Abdi Pradnyani; I Gusti Ayu Astri Pramitari (P3M Politeknik Negeri Bali, 2019)
Abstract. This study aims to determine the effect of online trading facilities and minimal capital investment on students interest to invest in the capital market. Various external and internal factors that arise that can affect the interests of potential young investors in investing in the capital market. As technology-savvy millennials and most of them are not yet earning, several factors including the existence of online trading facilities and minimal investment capital will influence the interests of potential young investors in investing in the capital market. The population in this study are students who are still actively registered in the accounting department of the Bali State Polytechnic. The sample collection method used is a purposive sampling method with criteria, students majoring in accounting who have received capital market and investment courses. The number of samples in this study were 114 people. Data obtained in the form of answers from respondents and processed using SPSS. The results obtained in this study were from 114 samples who filled out the questionnaire, it was found that both the variables of online trading facilities and minimal capital investment had an influence on the investment interests of students of accounting department Bali State Polytechnic. Keywords: online trading facilities, minimal capital investment, investment interest, capital market. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh fasilitas online trading dan modal minimal investasi pada minat mahasiswa untuk berinvestasi pasar modal. Berbagai faktor baik external dan internal yang muncul yang dapat mempengaruhi minat calon investor muda dalam berinvestasi di pasar modal. Sebagai kaum milenial yang melek teknologi dan sebagian besar belum berpenghasilan, beberapa faktor antara lain adanya fasilitas online trading dan modal minimal investasi akan mempengaruhi minat para calon investor muda dalam berinvestasi di pasar modal. Populasi dalam penelitian ini adalah mahasiswa yang masih terdaftar aktif di jurusan akuntansi Politeknik Negeri Bali. Metode pengumpulan sample yang digunakan adalah metode purposive sampling dengan kriteria yaitu mahasiswa jurusan akuntansi yang sudah mendapatkan mata kuliah pasar modal dan investasi. Adapun jumlah sample dalam penelitian ini adalah 114 orang. Data diperoleh berupa jawaban dari responden dan diolah menggunakan SPSS. Adapun hasil yang didapatkan dalam penelitian ini adalah dari 114 orang sample yang mengisi kuisioner, didapatkan hasil bahwa baik variable fasilitas online trading dan modal minimal investasi memiliki pengaruh pada minat investasi mahasiswa Jurusan Akuntansi Politeknik Negeri Bali. Kata Kunci: fasilitas online trading, modal minimal investasi, minat investasi, pasar modal.